Systematic Review and Meta-Analysis of Token Economy Practices in K-5 Educational Settings, 2000 to 2019. Issue 6 (November 2022) - Kim, Ji Young; Fienup, Daniel M.; Oh, Alice E.; Wang, Ye
Token economy systems have been widely used as an evidence-based classroom management strategy to reinforce and improve prosocial responses. While token economies have been widely applied to educational settings, there have been mixed results regarding the effectiveness depending on the classroom type. To better understand the components contributing to the effectiveness, the researchers analyzed 24 token economy studies conducted in general and special education classrooms from kindergarten to fifth grade between 2000 and 2019. Eight token economy components and effect sizes were identified for each study and compared across different classroom types. The results showed that the token economy intervention yielded large effect sizes for both general and special education classroom types. There were differences in the usage of token components including backup reinforcer types, token production rate, and exchange production rate based on classroom types. Implications for future research and practice for educators and clinicians are discussed.